O impacto de aspectos internos e externos no desempenho das subsidiárias de empresas Multinacionais em período de crise econômica - Cordeiro, Matheus Baldo (2016)
In an increasingly globalized world, firm internationalization has become a major strategy for companies to be competitive in the market. However, firms are facing turbulent times such as economic crisis. The recession effects are extensively studied in the economic field and it proves that these periods are inevitable. Nonetheless, there is a lack of studies in the management field, considering the economic crisis effects, and even more particularly, focusing on the multinational enterprises’ subsidiaries performance during recession times. This study intends to analyze and comprehend which are the relevant aspects for these subsidiaries to achieve a good performance and, therefore, they remain competitive during economic crisis in the market they operate. To investigate the effect, we analyze the case of Japanese subsidiaries located in the European market during pre-crisis and post-crisis, that started in the US and spread all over the world. It was used longitudinal data including the years between 2006 and 2013. A linear regression with panel data and fixed effects had been applied to generate the models used for the analysis. The results show how internal aspects related to accumulated experience, entry mode considering the same nationality of partners and the amount of expatriated staffs, as well as macroeconomic external aspects involving low inflation rate and population income indicators, impacted positively in the Japanese subsidiary performance during crisis periods. The performance is also higher when considering pre-crisis period.